Prevalence of Lower Urinary Tract Symptoms In Elderly Men Above 50 Years of Age (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To assess the prevalence of lower urinary tract symptoms in the hospital attendants population. Subjects and Methods: One thousand males, above 50 years of age, attending their patients at Services Hospital Lahore, were interviewed with a questionnaire. The questionnaire comprises International prostate symptom score (IPSS) questionnaire. The persons who were known caseS of Diabetes mellitus, Congestive cardiac failure, Neurogenic bladder, vesical stone or stone in lower ureter, urinary tract infection, urinary bladder growth or patients who were taking drugs which effect urinary system were excluded from the study. Results: Lower urinary tract symptoms were common and increased with increase in age. The prevalence of at least one urinary symptom was 53.7 % in men over 50 years of age ( 51.7 % among 51-60 years old men, 62.04 % among 61-70 years old men and 71.43 % in 70 years and above old men). Most of the symptoms were mild with nocturia most prevalent and urge incontinence (an additional symptom not included in IPSS score chart) the least. Conclusion: The high incidence of lower urinary tract symptoms may indicate high prevalence of benign prostatic enlargement, but other causes are also involved. With the increase in the mean age of the general population, the number of individuals with lower urinary tract symptoms is likely to increase. As lower urinary tract symptoms adversely affect quality of life, improved treatment options and increased public awareness of benign prostatic hypertrophy and lower urinary tract symptoms are needed to combat a problem facing the growing number of elderly men in the population.
Keywords: BPH, Lower urinary tract symptoms, Prevalence.